Positive regulation of innate immune response by miRNA-let-7a-5p - Mayumi Ueta; Hiromi Nishigaki; Seitaro Komai; Katsura Mizushima; Risa Tamagawa-Mineoka; Yuji Naito; Norito Katoh; Chie Sotozono; Shigeru Kinoshita (Frontiers in Genetics, 2023)
Background: We have hypothesized that different factors are involved in the severity of ACD and AD because some but not all patients with atopic dermatitis (AD) present with allergic conjunctival disease (ACD) including severe types such as atopic keratoconjunctivitis (AKC) with/without giant papillae. We previously reported that plasma miR-628-3p was up-regulated in AD with severe ACD, but not in severe AD without severe ACD or in our healthy controls. In this study, to investigate the pathogenesis of AD with and without severe ACD, we performed comprehensive plasma miRNA analysis and studied the function of some miRNAs which were significantly up-regulated in ACD.Methods: Transcriptomics analysis of miRNA was performed using the microarray platform from the plasma of nine individuals (AD, severe ACD, controls: n = 3 each). To confirm up-regulation of the 12 miRNAs of the eight miRNA groups we focused on, we performed quantitative miRNA polymerase chain reaction (PCR) assays using 80 plasma samples (AD: 23, severe ACD: 17, controls: 40). To study the function of the eight miRNAs which were significantly up-regulated in ACD, we transfected their mimic to THP-1 cells, a monocyte cell line, and performed comprehensive gene expression analysis of them. The up-regulation of gene expression of interest in transfected THP-1 cells with the hsa-let-7a-5p miRNA mimic was confirmed by quantitative RT-qPCR assay.Results: Quantitative miRNA PCR assays showed that hsa-let-7a-5p, hsa-let-7days-3p, hsa-let-7e-5p, and hsa-miR-151a-5p were significantly up-regulated in both AD-ACD+ and AD-ACD- as were hsa-miR-130a-3p, hsa-miR-151a-3p, has-miR-27b-3p, and hsa-miR-146a-5p in AD-ACD+ but not in AD-ACD-. The functions of each miRNA were investigated by comprehensive gene expression analysis of THP-1 cells transfected with each miRNA mimic. Of the eight miRNAs, hsa-let-7a-5p, hsa-let-7e-5p, has-miR-27b-3p, and hsa-miR-146a-5p mimic-transfected THP-1 cells showed the up-regulation of CXCL10 (IP-10; interferon gamma-induced protein 10), which might be one of the innate immune-related genes. Quantitative RT-qPCR assays of transfected THP-1 cells with the hsa-let-7a-5p miRNA mimic showed that the 17 genes up-regulated more than 10-fold in the comprehensive gene expression analysis, and TLR3, RIG-I, and MDA5, important innate immune-related genes, were significantly up-regulated. TNFSF13B, AIM2, USP41, STAP1, GBP4, CCL8, and IFI27, reportedly down-regulated by the hsa-miR-628-3p mimic, were also significantly up-regulated in the transfected cells.Conclusion: Hsa-let-7a-5p, which was significantly up-regulated in AD-ACD+ and AD-ACD-, could positively regulate the important innate immune-related genes such as TLR3, RIG-I, and MDA5. It is possible that in an allergic disease such as atopic keratoconjunctivitis and/or dermatitis, innate immune responses might be positively regulated by hsa-let-7a-5p in the plasma.